The effectiveness of fiscal-budgetary measures to counteract the COVID-19 crisis: Evidence from EU countries - Adina Dornean; Dumitru-Cristian Oanea (Economics: The Open-Access, Open-Assessment Journal, 2022)
The aim of this study is to analyse the fiscal-budgetary measures, which have been taken by almost all governments around the world, including EU countries, in an attempt to limit the negative impact of the pandemic blockade. In most cases, these measures concerned the granting of technical unemployment, the postponement of tax payments, and the suspension or postponement of loan instalments or their maturity. The present study focuses especially on tax and expenditure measures that EU countries have introduced in response to the COVID-19 crisis. With this purpose, a paired sample t -test and multiple linear regression are used based on balanced panel data for the 27 EU countries for the period 2000Q1-2020Q3. The obtained results show that COVID-19 crisis had a significant negative impact on GDP growth. At the same time, a significant increase in public debt and government deficit occurred due to COVID-19 crisis. However, resuming the findings, the intensity, and implicitly, the effect of these measures depends on the specifics of each economy.
Keywords: C33; E62; H25; O11; O52; 330; COVID-19 crisis; expenditure measures; tax measures